Antimicrobial Effects of SeptiTurbo, Deconex (Solarsept) and 0.525% Sodium Hypochlorite Spray on Alginate Impression Materials - Hemmati, Mohammad Ali; Felegari, Mehdi; Vakili, Rosita; Sharif Asgari, Morteza; Kermanjani, Ali; Norouzi, Mehdi (Journal of Dental School, 2019)
Objectives: Dental impressions are among the potentially infectious items in dentistry. Dental impressions are invariably contaminated with saliva or blood. Such fluids may contain viral or bacterial pathogens including Bacteroides, Fusobacterium, Porphyromonas and Prevotella. The aim of this study was to assess the effects of three different types of disinfectants on alginate impression materials after one, three and five minutes. Methods: In this in vitro experimental study, 126 circular samples of alginate impression materials were contaminated with Staphylococcus aureus (S. aureus) and Pseudomonas aeruginosa and were then disinfected with 0.525% sodium hypochlorite, Deconex (Solarsept) and SeptiTurbo spray. Afterwards, the samples were wrapped in moist paper towels and kept in plastic bags for one, three and five minutes. Number of bacterial colonies was counted 24 hours after incubation. Negative and positive controls were included. Results: After five minutes, 0.525% sodium hypochlorite showed the highest disinfection activity against S. aurous as it eradicated over 99.98% of the bacteria. Although the disinfecting agents showed non-significant results in eradicating S. aureus, SeptiTurbo was more effective in elimination of S. aurous . The disinfection activity of different agents increased with time. Conclusion: This study revealed that alginate can be effectively disinfected with SeptiTurbo and sodium hypochlorite by the spraying technique. This study highlighted the efficacy of SeptiTurbo for eradication of S. aurous.